Method for preparing modified silicon-carbon composite material and modified silicon-carbon composite material

The modified silicon-carbon composite material is formed through acidified carbon nanotubes, nanosilicon particles and chemical vapor deposition technology, which solves the problem of structural instability of silicon-carbon composite materials during charging and discharging, improves electrochemical performance and cyclic stability, and enhances the energy and power density of the battery.

CN120376615APending Publication Date: 2025-07-25JIANGXI OPT IND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510531657.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-25
Publication Date
2025-07-25

AI Technical Summary

Technical Problem

In the prior art, the silicon-carbon composite material has a structural instability due to volume changes during charging and discharging, and the lack of effective combination between silicon and carbon materials, affecting the electrochemical performance and cyclic stability, making it difficult to meet the needs of high-performance electrode materials.

Method used

By acidizing carbon nanotubes, grafting amino mono-terminated polydimethylsiloxane, nanosilicon particles and forming a three-dimensional network structure through chemical vapor deposition technology. Combined with sintering treatment, the effective bonding and stability of silicon and carbon materials are ensured.

Benefits of technology

It improves the conductivity, structural stability and electrochemical properties of the material, extends the service life of the battery, and enhances the energy and power density of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120376615A_ABST
    Figure CN120376615A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of modified silicon-carbon composite materials, in particular to a method for preparing a modified silicon-carbon composite material and the modified silicon-carbon composite material, and the method comprises the following steps: step 1, acidifying carbon nanotubes (CNTs); step 2, preparing a CNTs-APS compound; step 3, preparing nano silicon; 4, preparing a modified silicon-carbon composite material; step 5, sintering processing; organosilane reacts with active functional groups on the surface of a CNTs-APS compound by utilizing a chemical vapor deposition technology, and a carbon material is connected to the surfaces of nano silicon particles by taking organosilane as a bridge to form a three-dimensional network structure, so that the mechanical property and the thermal stability of the material are improved, and the binding force between the CNTs-APS compound and the surfaces of the nano silicon particles is also enhanced; impurities and oxygen functional groups on the surface of the carbon nano tube are removed by acidizing the carbon nano tube, the chemical activity of the surface of the carbon nano tube is improved, the activity of the surface of the carbon material is fully utilized, and then the bonding performance of the carbon nano tube and silicon is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of modified silicon-carbon composite materials, and specifically to a method for preparing a modified silicon-carbon composite material and the modified silicon-carbon composite material. Background Art

[0002] In the preparation of battery electrode materials, silicon-carbon composite materials have received extensive research and application due to their excellent electrochemical performance, especially high specific capacity and good cycle stability. Silicon, due to its high theoretical specific capacity, approximately 10 times the theoretical lithium capacity, i.e., 4200 mAh / g, is considered one of the ideal choices for future high-performance electrode materials. However, silicon undergoes significant volume changes during the charge-discharge cycle, approximately 300%, which leads to instability of the electrode structure, significant volume changes during the charge-discharge process, resulting in structural damage of the material, degradation of the cycle performance, and fatal electrode-electrolyte interface problems. Therefore, how to improve the structural stability and electrochemical performance of silicon-based electrodes has become the research focus.

[0003] In recent years, modifying silicon-carbon composite materials by chemical or physical methods to improve their electrochemical performance and cycle stability has become a research hotspot. However, in the prior art, the physical mixing method results in a lack of effective bonding between the silicon and carbon materials, easily leading to separation between the materials due to the stress caused by the volume expansion and contraction of silicon during the charge-discharge process, thus reducing the structural stability. In addition, the traditional mixing method is difficult to ensure the full utilization of the activity on the surface of silicon particles or carbon materials, resulting in low activity during the electrochemical reaction process and also affecting the improvement of battery performance, making it difficult to meet the requirements of emerging energy storage technologies for high-performance electrode materials. Summary of the Invention

[0004] The purpose of the present invention is to provide a method for preparing a modified silicon-carbon composite material and the modified silicon-carbon composite material to solve the problems raised in the above background art.

[0005] To achieve the above purpose, the present invention provides the following technical solutions: A method for preparing a modified silicon-carbon composite material and the modified silicon-carbon composite material, including the following steps: Step 1, acidifying carbon nanotubes CNTs; Step 2, preparing a CNTs-APS composite; Step 3, preparing nanosized silicon; Step 4, preparing a modified silicon-carbon composite material; Step 5, sintering and processing; The specific steps are as follows:

[0006] Step 1: Acidify carbon nanotubes (CNTs). Place the CNTs in a mixed acid solution and react under the condition of an ultrasonic bath. Soak at room temperature for 18 hours to allow the acid solution to react with the carbon atoms on the surface of the carbon nanotubes, causing the carbon-carbon bonds on the surface of the carbon nanotubes to break, and then forming functional groups such as hydroxyl and carboxyl groups. After the reaction is completed, dilute with deionized water and filter under reduced pressure, then wash with deionized water until neutral, and finally dry to obtain acidified carbon nanotubes;

[0007] Step 2: By using the chemical reaction between acidified CNTs, N,N'-carbonyldiimidazole (CDI), and amino-terminated polydimethylsiloxane (APS), APS can be successfully grafted onto the surface of CNTs, thereby preparing a CNT-APS composite with unique structures and properties;

[0008] Step 3: Nanometerize silicon particles. Use a ball milling method combined with vacuum heating to nanometerize silicon particles. The specific steps are as follows:

[0009] Ball mill silicon particles:

[0010] Raw material preparation: Select high-purity silicon powder as the raw material to ensure the purity and performance of the prepared nanosilicon particles;

[0011] Ball milling process: Put the silicon powder into a ball mill, add ethanol as a lubricant, and then add grinding media for ball milling. During the ball milling process, the grinding media impact, shear, and grind the silicon powder, gradually refining it to 85 nm nanosilicon;

[0012] Collection and treatment: After ball milling, separate the nanosilicon particles from the grinding media and lubricant by filtration, washing, and drying at 85 °C to obtain pure nanosilicon particles;

[0013] Vacuum heat treatment:

[0014] Put the collected nanosilicon particles into a vacuum heat treatment device, use the built-in vacuum pump of the vacuum heat treatment device to pre-pump the vacuum, then fill with an inert gas, and finally reach a vacuum degree of 0.5 Pa;

[0015] Start the heating system of the vacuum heat treatment device to heat the nanosilicon particles, and the heating process is carried out in stages;

[0016] Step 4: Use chemical vapor deposition (CVD) technology to react the functional connecting end of organosilane with the active functional groups on the surface of the CNT-APS composite, so that the carbon material is connected to the silicon surface to form a modified silicon-carbon composite material;

[0017] Introduce organosilane into the reaction chamber. When the substrate is heated to 800 - 1000 °C, the organosilane becomes activated and releases free silicon functional groups. The silicon functional groups undergo an addition reaction with the active groups on the carbon atoms of the CNTs-APS composite, forming silicon-carbon covalent bonds. The silicon atoms of the nanosilicon particles can directly bind to the carbon atoms on the surface of the CNTs-APS composite through silicon-carbon covalent bonds, enabling the silicon functional groups to selectively and precisely connect the CNTs-APS composite to the upper surface of the nanosilicon particles, forming a silicon-carbon composite material;

[0018] Place the reacted silicon-carbon composite material in a silane solvent, and conduct sufficient stirring or ultrasonic treatment to promote the dissolution and dispersion of unreacted silane and impurities. After the cleaning is completed, separate the silicon-carbon composite material from the solvent by filtration, and then use vacuum drying to rapidly dry the silicon-carbon composite material at a relatively low temperature, which helps to reduce the thermal damage of the silicon-carbon composite material. The dried silicon-carbon composite material is subjected to screening treatment to obtain the silicon-carbon composite material with the desired particle size and shape;

[0019] Step Five: Put the silicon-carbon composite material into a sintering device. Use a vacuum pumping device to extract the air pressure inside the sintering device, and then fill the inside of the sintering device with nitrogen to make the vacuum degree inside the sintering device reach 0.5 Pa. Control the heating system to slowly heat to 750 °C. When the required temperature is reached, the material will continue to stay at this temperature for 6 hours to ensure that a sufficient sintering reaction is completed. By controlling appropriate sintering conditions, such as temperature, time, and atmosphere, ensure that the material can be fully sintered without damaging its structural integrity.

[0020] Preferably, in Step One, the mixed acid solution uses concentrated sulfuric acid and concentrated nitric acid, and the volume ratio of concentrated sulfuric acid to concentrated nitric acid is 3:1.

[0021] Preferably, in Step Three, the staged heating process: the first stage is to raise the temperature to 200 °C to 400 °C and conduct heat treatment for 18 hours; the second stage is to raise the temperature to 400 °C to 600 °C and conduct heat treatment for 8 hours; the third stage is to raise the temperature to 600 °C to 900 °C and conduct heat treatment for 3 hours;

[0022] Preferably, in Step Three, the inert gas uses nitrogen to conduct heat treatment on the nanosilicon particles under the protection of nitrogen.

[0023] Preferably, in Step Three, the rotation speed of the ball mill is 2000 r / min, ball milling is carried out for 18 hours, and the particle size of the steel balls used for ball milling is 0.2 mm.

[0024] Preferably, in Step Five, the vacuum degree inside the sintering device reaches 0.5 Pa, the heating temperature is 750 °C, the slow heating time is 8 hours, and it stays at 750 °C for 6 hours.

[0025] Compared with the prior art, the beneficial effects of the present invention are as follows: By acidifying carbon nanotubes, the impurities and oxygen functional groups on their surfaces are removed, improving their surface chemical activity, ensuring that the activity of the carbon material surface is fully utilized, thereby improving the interfacial contact between carbon nanotubes and silicon materials, enhancing the bonding performance between carbon nanotubes and silicon, and enhancing the electrical conductivity and mechanical properties of the composite material; Using a chemical reaction to graft amino-terminated polydimethylsiloxane APS onto the acidified carbon nanotubes to form a unique CNTs-APS composite. This composite not only has excellent electrical conductivity but also enhances the structural stability of the composite material; The silicon particles prepared by the nanosizing technology can greatly reduce the damage caused by volume expansion, improve the material utilization rate and electrochemical performance. The nanosilicon particles are ball-milled and vacuum heat-treated to form a stable SEI film on their surfaces and eliminate internal stress, thereby reducing the volume change during charge and discharge, enhancing the uniform dispersion between particles, reducing local stress concentration, and effectively reducing cracking and grain segregation; Using chemical vapor deposition technology to react organosilane with the active functional groups on the surface of the CNTs-APS composite, and connecting the carbon material to the surface of the nanosilicon particles through organosilane as a bridge to form a three-dimensional network structure. The three-dimensional network structure not only improves the mechanical properties and thermal stability of the material but also enhances the bonding force between the CNTs-APS composite and the surface of the nanosilicon particles, solving the problem that the lack of effective bonding between the two materials of silicon and carbon in the physical mixing method easily leads to the separation of the materials caused by the stress caused by the volume expansion and contraction of silicon during charge and discharge; And the CNTs-APS composite coats the nanosilicon particles to form a carbon network protection layer. Electrons can freely flow in the conductive carbon network structure, reducing the resistance between the nanosilicon particles, thereby achieving an increase in electrical conductivity and an improvement in the overall energy conversion efficiency; The carbon network protection layer can effectively disperse the volume change of the silicon particles, slow down the mechanical stress of the material, and at the same time form a more stable electrode interface, reducing the contact with harmful substances in the electrochemical process, reducing the negative impact caused by the decomposition of the electrolyte, thereby prolonging the service life of the material during charge and discharge, increasing the battery energy density and power density; By sintering treatment, the residues in the deposition process are removed, improving the density of the material and further improving its mechanical properties, so that the modified silicon-carbon composite material has excellent electrical conductivity, mechanical properties and thermal stability, greatly improving the energy density and power density of the battery and prolonging its service life. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 is the preparation flow chart of the present invention;

[0027] Figure 2 is the preparation flow chart of the CNTs-APS composite of the present invention;

[0028] Figure 3 Flow chart for preparing nanosilicon according to the present invention;

[0029] Figure 4 Flow chart for preparing modified silicon-carbon composite material according to the present invention. Specific embodiments

[0030] Next, the technical solutions in the embodiments of the present invention will be clearly and completely described in conjunction with the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts shall fall within the protection scope of the present invention.

[0031] Please refer to Figures 1-4 , a technical solution provided by the present invention:

[0032] Example:

[0033] A method for preparing a modified silicon-carbon composite material and the modified silicon-carbon composite material proposed by the present invention are characterized by including the following steps: Step 1, acidifying carbon nanotubes CNTs; Step 2, preparing CNTs-APS composite; Step 3, preparing nanosilicon; Step 4, preparing modified silicon-carbon composite material; Step 5, sintering and processing; The specific steps are as follows:

[0034] Step 1: Acidify carbon nanotubes CNTs. Place the CNTs in a mixed acid solution. The mixed acid solution uses concentrated sulfuric acid and concentrated nitric acid, and the volume ratio of concentrated sulfuric acid to concentrated nitric acid is 3:1. React under the condition of an ultrasonic bath and soak at room temperature for 18 hours, so that the carbon atoms on the surface of the acid solution and the carbon nanotubes react, resulting in the breakage of the carbon-carbon bonds on the surface of the carbon nanotubes, and then forming functional groups such as hydroxyl and carboxyl groups. The formation of functional groups such as hydroxyl and carboxyl groups on the surface of the carbon nanotubes not only improves the liquid absorption capacity and conductivity of the carbon nanotubes, but also improves their interfacial bonding ability with other materials;

[0035] After the reaction is completed, dilute with deionized water and perform vacuum filtration, then wash with deionized water until neutral, and finally dry in a low-temperature environment at 35°C to obtain acidified carbon nanotubes. The acidified carbon nanotubes can help improve the conductivity and mechanical properties of the composite material, and indirectly enhance the safety of the composite material while improving the battery performance;

[0036] Step 2: By using the chemical reaction between acidified CNTs, N,N'-carbonyldiimidazole CDI and amino-monofunctionalized polydimethylsiloxane APS, APS can be successfully grafted onto the surface of CNTs, thereby preparing a CNTs-APS composite with unique structure and properties. The specific steps are as follows:

[0037] The acidified CNTs were added to dimethyl sulfoxide, and after ultrasonic dispersion, CDI was added. The temperature was raised to 65 °C and stirred for 8 hours, then APS was added. The weight ratio of CNTs, CDI, and APS was 2:0.3:8. The reaction was stirred at 55 °C for 20 hours. After the reaction, extraction was carried out with acetone at 65 °C for 35 h, and drying was carried out at a low temperature of 65 °C to obtain an intermediate product;

[0038] The intermediate product, nano-iron oxide, and nano-lanthanum oxide were added to absolute ethanol. The weight ratio of the intermediate product, nano-iron oxide, and nano-lanthanum oxide was 2:3:1. After the temperature was raised to 55 °C, ultrasonic reaction was carried out for 8 hours. After the reaction, filtration was carried out by a centrifuge, followed by washing with deionized water, and then drying was carried out at a low temperature of 65 °C to obtain the CNTs-APS composite;

[0039] Step 3: Nanostructuring of silicon particles. The silicon particles were nanostructured by a method combining ball milling and vacuum heating, and the following steps were specifically adopted:

[0040] Ball milling of silicon particles:

[0041] Raw material preparation: High-purity silicon powder was selected as the raw material to ensure the purity and performance of the prepared nano-silicon particles;

[0042] Ball milling process: 5-micron silicon powder was put into a ball mill, ethanol was added as a lubricant, and then a grinding medium with a steel ball diameter of 0.2 mm was added for ball milling. The rotation speed of the ball mill was 2000 r / min, and ball milling was carried out for 18 hours. During the ball milling process, the grinding medium impacted, sheared, and ground the silicon powder, gradually refining it to 85-nm nano-silicon;

[0043] Collection and treatment: After ball milling, the nano-silicon particles were separated from the grinding medium and lubricant by filtration, washing, and drying at a temperature of 85 °C to obtain pure nano-silicon particles;

[0044] Nanostructuring of silicon particles can significantly reduce the volume change of silicon during charge and discharge. A relatively thin SEI film is formed on the outer surface of the nano-particle silicon. The presence of the SEI film helps to reduce the direct reaction between silicon and the electrolyte, thereby extending the life of the battery. Moreover, the nano-scale silicon particles have a smaller size, and the volume change generated during the charge and discharge cycle is more uniform, and it is not easy to form local stress concentration points in the electrode, thereby reducing the formation of cracks;

[0045] Vacuum heat treatment:

[0046] Put the collected nano-silicon particles into a vacuum heat processor, and use the built-in vacuum pump of the vacuum heat processor to pre-pump the vacuum. Subsequently, an inert gas is filled. Here, the inert gas is nitrogen. The nano-silicon particles are heat-treated under the protection of nitrogen. By filling nitrogen, the moisture in the vacuum heat processor is discharged to reduce the contamination of the nano-silicon particles by moisture and to provide heating protection for the heat-treated nano-silicon particles, which can avoid the interference of oxygen and the oxidation of the particles. Filling the inert gas makes the vacuum degree in the vacuum heat processor finally reach 0.5 Pa;

[0047] Then start the heating system of the vacuum heat processor to heat the nano-silicon particles. The heating process is carried out in stages. In the first stage, the temperature is raised to 200 °C to 400 °C and heat-treated for 18 hours. In the second stage, the temperature is raised to 400 °C to 600 °C and heat-treated for 8 hours. In the third stage, the temperature is raised to 600 °C to 900 °C and heat-treated for 3 hours;

[0048] Among them, the first stage is a low-temperature holding stage. The temperature is raised to 300 °C in 18 hours and held at a low temperature for 18 hours to promote the volatilization and elimination of internal impurities in the material, release the internal stress of the silicon particles, and at the same time reduce the thermal shock effect caused by rapid heating, which helps to maintain the integrity of the silicon particles and avoid cracking during subsequent high-temperature treatment;

[0049] The second stage is a gradual heating stage: the temperature is gradually raised to 550 °C in 8 hours. Gradual heating can help avoid problems such as thermal stress concentration and non-uniform phase transformation caused by sudden temperature changes, and ensure that the nano-silicon particles maintain good uniformity and stability during the entire heating process;

[0050] The third stage is a high-temperature heat treatment stage. When the temperature is raised to 750 °C, continue to hold for 3 hours to ensure that the nano-silicon particles undergo a sufficient heat treatment process at this temperature, eliminate the internal defects and stress of the nano-silicon particles, improve their crystallinity and stability, so as to achieve the required physical or chemical property changes. And when the temperature rises to 750 °C, an oxidation reaction occurs on the surface of the silicon particles to form a protective silicon dioxide layer;

[0051] A large number of nano-silicon particles can be quickly prepared by the ball milling method, and the particle dispersion can be further improved by staged heat treatment, eliminating small cracks or surface defects generated during the ball milling process, improving crystallinity and stability, thereby optimizing the electrochemical performance of the silicon nanoparticles, improving the cycle stability and capacity retention rate of the silicon nanoparticles in battery applications, and also helping the nanoparticles to maintain good structural stability and material properties during subsequent high-temperature heat treatment. The combination of the two can efficiently prepare high-quality nano-silicon particles;

[0052] Step 4: Use chemical vapor deposition (CVD) technology to react the functional linking ends of organosilanes with the reactive functional groups on the surface of the CNTs-APS composite, so that the carbon material is connected to the silicon surface to form a modified silicon-carbon composite material. The specific steps are as follows:

[0053] Introduce organosilane into the reaction chamber. When the substrate is heated to 800 - 1000 °C, the organosilane is activated and releases free silicon functional groups. The silicon functional groups undergo an addition reaction with the reactive groups on the carbon atoms of the CNTs-APS composite to form silicon-carbon covalent bonds. The silicon atoms of the nanosilicon particles can directly bind to the carbon atoms on the surface of the CNTs-APS composite through silicon-carbon covalent bonds, enabling the silicon functional groups to selectively and precisely connect the CNTs-APS composite to the upper surface of the nanosilicon particles to form a modified silicon-carbon composite material;

[0054] Place the reacted modified silicon-carbon composite material in a silane solvent and perform ultrasonic treatment for 2 hours to promote the dissolution and dispersion of unreacted silane and impurities, and wash out the unreacted silane and impurities through the silane solvent; after the washing is completed, separate the silicon-carbon composite material from the solvent by filtration, and then adopt a vacuum drying method with a vacuum degree maintained at 0.5 Pa and a temperature controlled at 35 °C for 2 hours to achieve rapid drying of the silicon-carbon composite material at a relatively low temperature, which helps to reduce the thermal damage of the silicon-carbon composite material. The dried silicon-carbon composite material is subjected to screening treatment to obtain the silicon-carbon composite material with the desired particle size and shape;

[0055] During the process of raw material compounding, compounding nanosilicon particles with the CNTs-APS composite can improve the conductivity of the electrode, which helps to improve the cycling performance of half-cells and full-cells. The specific surface area of the nanoparticles is relatively large, which helps to increase the contact ratio of the electrolyte and increase the channels for electrons to diffuse through the electrode; and through organosilane as a bridge, a covalent bond connection is formed between silicon and carbon. This connection is not only stable but also can change the properties of organosilane through chemical modification, such as hydrophilicity / hydrophobicity, light stability, and conductivity;

[0056] Step Five: Put the silicon-carbon composite material into the sintering equipment. Use a vacuum pumping device to extract the air pressure inside the sintering equipment, and then fill the inside of the sintering equipment with nitrogen to make the vacuum degree inside the sintering equipment reach 0.5 Pa. The vacuum and nitrogen environment can prevent the material from adsorbing other pollutants or gases, thereby accelerating the volatilization of residual impurities. Then control the heating system to slowly heat to 750 °C. When the required temperature is reached, the material will stay at this temperature for 6 hours to ensure that a sufficient sintering reaction is completed to remove unreacted silane and impurities. The slow and continuous heating process ensures that different parts inside the material can be evenly heated, thereby maximizing the density and reducing defects such as pores. By controlling appropriate sintering conditions, such as temperature, time, and atmosphere, ensure that the material can be fully sintered without damaging its structural integrity, thereby greatly reducing the gas volatiles and other impurities that may exist in the material.

[0057] For those skilled in the art, it is obvious that the present invention is not limited to the details of the above exemplary embodiments, and without departing from the spirit or basic characteristics of the present invention, the present invention can be implemented in other specific forms. Therefore, from any point of view, the embodiments should be regarded as exemplary and non-restrictive. The scope of the present invention is defined by the appended claims rather than the above description. Therefore, all changes falling within the meaning and scope of the equivalent elements of the claims are intended to be included in the present invention. Any reference signs in the claims should not be regarded as limiting the claims involved.

Claims

1. A method for preparing a modified silicon-carbon composite material and the modified silicon-carbon composite material, characterized in that, It includes the following steps: Step 1, acidify carbon nanotubes CNTs; Step 2, prepare CNTs-APS composite; Step 3, prepare nano-sized silicon; Step 4, prepare modified silicon-carbon composite; Step 5, sinter and process; The specific steps are as follows: Step 1: Acidify carbon nanotubes CNTs. Place the CNTs in a mixed acid solution and react under the condition of an ultrasonic bath. Soak at room temperature for 18 hours to cause the carbon atoms on the surface of the carbon nanotubes to react with the acid solution, resulting in the breakage of carbon-carbon bonds on the surface of the carbon nanotubes, and then functional groups such as hydroxyl and carboxyl groups are formed. After the reaction is completed, dilute with deionized water and filter under reduced pressure, then wash with deionized water until neutral, and finally dry to obtain acidified carbon nanotubes; Step 2: By using the chemical reaction between acidified CNTs, N,N'-carbonyldiimidazole CDI, and amino-terminated polydimethylsiloxane APS, APS can be successfully grafted onto the surface of CNTs, thereby preparing a CNTs-APS composite with unique structures and properties; Step 3: Nanometerize silicon particles. Adopt the method of ball milling combined with vacuum heating to nanometerize silicon particles. The specific steps are as follows: Ball mill silicon particles: Raw material preparation: Select high-purity silicon powder as the raw material to ensure the purity and performance of the prepared nano-silicon particles; Ball milling process: Put the silicon powder into a ball mill, add ethanol as a lubricant, and then add grinding media for ball milling. During the ball milling process, the grinding media impact, shear, and grind the silicon powder, gradually refining it to 85nm nano-silicon; Collection and treatment: After the ball milling is completed, separate the nano-silicon particles from the grinding media and lubricant by filtration, washing, and drying at 85°C to obtain pure nano-silicon particles; Vacuum heat treatment: Put the collected nano-silicon particles into a vacuum heat treatment device, use the built-in vacuum pump of the vacuum heat treatment device to pre-pump the vacuum, then fill with an inert gas, and finally reach a vacuum degree of 0.5Pa; Start the heating system of the vacuum heat treatment device to heat the nano-silicon particles. The heating process is carried out in stages; Step 4: Use chemical vapor deposition technology CVD to react the functional connecting end of organosilane with the active functional groups on the surface of the CNTs-APS composite, so that the carbon material is connected to the silicon surface to form a modified silicon-carbon composite; Introduce organosilane into the reaction chamber. When the substrate is heated to 800-1000°C, the organosilane is activated and releases free silicon functional groups. The silicon functional groups undergo an addition reaction with the active groups on the carbon atoms of the CNTs-APS composite to form a silicon-carbon covalent bond. The silicon atoms of the nano-silicon particles can directly combine with the carbon atoms on the surface of the CNTs-APS composite through the silicon-carbon covalent bond, enabling the silicon functional groups to selectively and precisely connect the CNTs-APS composite to the upper surface of the nano-silicon particles to form a silicon-carbon composite; The reacted silicon-carbon composite material is placed in a silane solvent and subjected to sufficient stirring or ultrasonic treatment to promote the dissolution and dispersion of unreacted silane and impurities. After the cleaning is completed, the silicon-carbon composite material is separated from the solvent by filtration, and then a vacuum drying method is used to rapidly dry the silicon-carbon composite material at a relatively low temperature of 75 °C, which helps to reduce the thermal damage of the silicon-carbon composite material. The dried silicon-carbon composite material is subjected to screening treatment to obtain the silicon-carbon composite material with the desired particle size and shape; Step Five: Put the silicon-carbon composite material into a sintering device. Use a vacuum pumping device to extract the air pressure inside the sintering device, and then fill the inside of the sintering device with nitrogen. Control the heating system to slowly heat up. When the required temperature is reached, maintain the temperature to ensure that a sufficient sintering reaction is completed to remove unreacted silane and impurities.

2. A method for preparing a modified silicon-carbon composite material and the modified silicon-carbon composite material according to claim 1, characterized in that: In Step One, the mixed acid solution uses concentrated sulfuric acid and concentrated nitric acid, and the volume ratio of concentrated sulfuric acid to concentrated nitric acid is 3:

1.

3. A method for preparing a modified silicon-carbon composite material according to claim 1, characterized in that: In Step Three, the staged heating process: In the first stage, the temperature is raised to 200 °C to 400 °C and heat-treated for 18 hours; in the second stage, the temperature is raised to 400 °C to 600 °C and heat-treated for 8 hours; In the third stage, the temperature is raised to 600 °C to 900 °C and heat-treated for 3 hours.

4. A method for preparing a modified silicon-carbon composite material and the modified silicon-carbon composite material according to claim 1, characterized in that: In Step Three, the inert gas uses nitrogen to heat-treat the nano-silicon particles under the protection of nitrogen.

5. A method for preparing a modified silicon-carbon composite material and the modified silicon-carbon composite material according to claim 1, characterized in that: In Step Three, the rotation speed of the ball mill is 2000 r / min, ball milling is carried out for 18 hours, and the particle size of the steel balls used for ball milling is 0.2 mm.

6. The method for preparing a modified silicon-carbon composite material and the modified silicon-carbon composite material according to claim 1, characterized in that: In Step Five, the vacuum degree inside the sintering device reaches 0.5 Pa, the heating temperature is 750 °C, the slow heating time is 8 hours, and it stays at 750 °C for 6 hours.